Identification of CDKN3 overexpression as a marker of poor prognosis and potential therapeutic target in low-grade glioma - Hongbing Cheng; Xiao Meng; Yanhua Zhang; Pu Wang; Yucheng Lu (Scientific Reports)
Abstract Low-grade glioma (LGG) is a primary, slow-growing brain tumor; however, its treatment and prognosis remain challenging. In this study, we analyzed cancer data from the TCGA database, focusing particularly on the expression of the CDKN3 gene in LGG. The results showed that high CDKN3 expression in LGG patients was significantly associated with poor survival outcomes. Further gene expression analysis revealed that 379 genes were significantly upregulated in LGG samples with high CDKN3 expression, and these genes were primarily involved in the mitotic cell cycle and extracellular matrix organization. Additionally, high CDKN3 expression was closely linked to key signaling pathways such as tumor inflammation, hypoxic response, and tumor proliferation. Immune microenvironment analysis showed that high CDKN3 expression significantly increased the expression of CD4 + T cells and specific immune checkpoint genes, suggesting a potentially poor response to immune checkpoint blockade therapy. Through in vitro and in vivo experiments, we confirmed that CDKN3 silencing significantly inhibited the proliferative capacity of LGG cells. Proteomics revealed that CDKN3 can bind ARG1 and inhibite the intracellular arginase activity. These findings not only improve our understanding of LGG biology but also provide scientific evidence for developing potential therapeutic strategies targeting CDKN3.